Dietary Supervisors. Senior Division. Curriculum RP-52 - Ontario Dept. of Education, Toronto; Ontario Dept. of Education, Toronto ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
GRADES OR AGES: Grades 11 and 12. SUBJECT MATTER: Dietetics and home economics. ORGANIZATION AND PHYSICAL APPEARANCE: The guide is divided into two parts. The first part outlines a 2-year course in dietetics, which is divided into ten units. The second part outlines a 1-year, grade 11 course in home economics which is divided into two sections, each of which is then divided into several units. All units are in list form. The guide is xeroxed and staple-bound with a paper cover. OBJECTIVES AND ACTIVITIES: Several objectives are listed at the beginning of each unit. No specific activities are mentioned; each unit contains detailed lists of topics to be covered. Suggestions are made for timing of units. INSTRUCTIONAL MATERIALS: Each unit and some subunits contain lists of related teacher and student references and films. STUDENT ASSESSMENT: No mention. (RT)
Educational level discussed: Grade 11.
Educational level discussed: Grade 12.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Guides; Dietetics; Grade 11.; Grade 12.; Home Economics